Organometallic chemistry, biology and medicine: ruthenium arene anticancer complexes - Yan, Yaw Kai; Melchart, Michael; Habtemariam, Abraha; Sadler, Peter J (Chemical communications (Cambridge, England), 2005)
Our work has shown that certain ruthenium(II) arene complexes exhibit promising anticancer activity in vitro and in vivo. The complexes are stable and water-soluble, and their frameworks provide considerable scope for optimising the design, both in terms of their biological activity and for minimising side-effects by variations in the arene and the other coordinated ligands. Initial studies on amino acids and nucleotides suggest that kinetic and thermodynamic control over a wide spectrum of reactions of Ru(II) arene complexes with biomolecules can be achieved. These Ru(II) arene complexes appear to have an altered profile of biological activity in comparison with metal-based anticancer complexes currently in clinical use or on clinical trial.